2021
DOI: 10.32598/ijmtfm.v11i1.32228
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Medicolegal Aspects of Fatal Imidacloprid Deliberate Self-poisoning: A Case Report

Abstract: Background: Imidacloprid is a neonicotinoid insecticide and agonist of nicotinic acetylcholine receptors. Despite its low toxicity profile, there are rare studies on its fatal poisoning. In this report, we described clinical and postmortem findings of a fatal imidacloprid poisoning. Methods: A 33-year-old female presented to the emergency department with a history of deliberate consumption of unknown insecticide. On admission, she was drowsy and hypotensive with tachycardia and miotic pupils. Despite supportiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Drowsiness, confusion, incoherence, lack of orientation, and unconsciousness after acute poisoning [101]. Somnolence, Glasgow Coma Scale with a score of 10/15 and Miotic pupils after acute poisoning [102].…”
Section: Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Drowsiness, confusion, incoherence, lack of orientation, and unconsciousness after acute poisoning [101]. Somnolence, Glasgow Coma Scale with a score of 10/15 and Miotic pupils after acute poisoning [102].…”
Section: Humansmentioning
confidence: 99%
“…In bats, it has been related to a decrease in proteins related to echolocation in different brain regions [95]. Moreover, in humans, acute imidacloprid poisonings have been associated with neurological signs such as dyspnea, coma, sweating, drowsiness, confusion, incoherence, lack of orientation, and miotic pupils, among others [100][101][102]. In an in vitro study with LUHMES and SH-SY5Y cells, an increase in intracellular calcium levels was found [123] (Table 5) On the other hand, after acute poisoning, cerebral edema has been reported as a necropsy finding [101], while in an in vitro study it was revealed that it can cause the death of SH-SY5Y cells [135].…”
Section: Imidaclopridmentioning
confidence: 99%